Enhancing the anti-tarnish and mechanical properties of gold-coated silver sheets for decorative applications using TiO2 film protection - Sarocha Khanwaeo; Pisan Srirach; Pichet Limsuwan; Aparporn Sakulkalavek; Rachsak Sakdanuphab (Results in Physics, 2024)
• TiO 2 coating inhibits Ag 2 S formation, enhancing tarnish resistance. • 20 nm TiO 2 layer maintains color properties with acceptable ΔE value. • TiO 2 reduces friction coefficient from 0.28 to 0.24, improving durability. • TiO 2 -coated samples retain 90% of coating after 1,000 abrasion cycles. This study explores an innovative method to enhance the anti-tarnish and mechanical properties of gold-coated silver sheets, targeting decorative applications through the TiO 2 film coatings. The research focuses on gold films with a thickness of approximately 100 nm, and TiO 2 films ranging from 10 to 31 nm. It was observed that the color of the multilayer coatings exhibited significant sensitivity to variations in thickness, indicating that a TiO 2 coating with a thickness around 20 nm could be optimally applied to the gold film, maintaining an acceptable ΔE value. X-ray photoelectron spectroscopy analysis demonstrated the TiO 2 film’s potential to inhibit the formation of Ag 2 S on the surface, thereby enhancing tarnish resistance. Furthermore, the application of a 20 nm TiO 2 layer reduced the friction coefficient from 0.28 to 0.24 for gold-coated silver. Durability tests involving 1,000 abrasion cycles revealed that the gold film without TiO 2 protection experienced delamination, with only about 57 % of the coated area remaining intact. In contrast, the samples protected with a TiO 2 layer retained approximately 90 % of the coating, underscoring the effectiveness of TiO 2 in preserving the structural integrity and appearance of the gold-coated silver sheets.
Keywords: TiO2 Photocatalysis and Solar Cells; Pigment Synthesis and Properties; Advanced Photocatalysis Techniques